Natural essential oils derived from herbal medicines: A promising therapy strategy for treating cognitive impairment - Shi, Ai; Long, Yu; Ma, Yin; Yu, Shuang; Li, Dan; Deng, Jie; Wen, Jing; Li, Xiaoqiu; Wu, Yuanyuan; He, Xiaofang; Hu, Yue; Li, Nan; et al. (Frontiers in Aging Neuroscience, 2023)
Cognitive impairment (CI), mainly Alzheimer’s disease (AD), continues to increase in prevalence and is emerging as one of the major health problems in society. However, until now, there are no first-line therapeutic agents for the allopathic treatment or reversal of the disease course. Therefore, the development of therapeutic modalities or drugs that are effective, easy to use, and suitable for long-term administration is important for the treatment of CI such as AD. Essential oils (EOs) extracted from natural herbs have a wide range of pharmacological components, low toxicity, and wide sources, In this review, we list the history of using volatile oils against cognitive disorders in several countries, summarize EOs and monomeric components with cognitive improvement effects, and find that they mainly act by attenuating the neurotoxicity of amyloid beta, anti-oxidative stress, modulating the central cholinergic system, and improving microglia-mediated neuroinflammation. And combined with aromatherapy, the unique advantages and potential of natural EOs in the treatment of AD and other disorders were discussed. This review hopes to provide scientific basis and new ideas for the development and application of natural medicine EOs in the treatment of CI.